Visible-light-initiated tandem synthesis of difluoromethylated oxindoles in 2-MeTHF under additive-, metal catalyst-, external photosensitizer-free and mild conditions - Gui, Qing-Wen; Teng, Fan; Li, Zhou-Chao; Xiong, Zhi-Yuan; Jin, Xue-Feng; Lin, Ying-Wu; Cao, Zhong; He, Wei-Min (Chinese chemical letters, 2021)
An efficient and eco-friendly protocol for synthesizing difluoromethylated oxindoles through a visible-light-induced one-pot tandem reaction of N-arylacrylamides, difluoroacetic acid and PhI(OAc)2 was developed. This reaction proceeded in the absence of any additive, base, metal-catalyst and external photosensitizer, using cheap CHF2CO2H as a difluoromethylation reagent and bulk biomass-derived 2-MeTHF as a solvent. [Display omitted] An efficient and eco-friendly protocol for synthesizing difluoromethylated oxindoles through a visible-light induced one-pot tandem reaction of N-arylacrylamides, difluoroacetic acid and PhI(OAc)2 was developed. This reaction proceeded in the absence of any additive, base, metal-catalyst and external photosensitizer, using cheap and easily available CHF2CO2H as the difluoromethylation reagent and bulk biomass-derived 2-MeTHF as the sole solvent. 26 Examples of N-arylacrylamide substrates were investigated, and all of them successfully underwent difluoromethylation to deliver the target products in good to excellent yields.